Fuel cell catalyst and method for producing same
By using specific chemical precursors and treatment methods in solid-state polymer fuel cells, the high density distribution of Pt nanowire particles on the support surface is solved, and the activity reduction caused by insufficient support density and Ni residue in the prior art is solved, achieving efficient catalytic performance.
Patent Information
- Application Number
- JP2021022411
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-29
- Filing Date
- 2021-02-16
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-02-16
AI Technical Summary
The prior art is difficult to support Pt nanowire particles in high density in solid polymer fuel cells, and it is easy to reduce activity and contamination due to the residue of Ni in the catalyst.
By dispersing in Oleming with Pt precursor, Ni precursor, W(CO)6 and /or Mo(CO)6, the reaction temperature and time were controlled, partial surface modification and washing were performed to ensure high density support of the nanowire particles on the support surface and Ni residue was removed by acid treatment.
The high-density support of nanowire particles on the support surface is achieved, reducing catalyst aggregation and contamination, and improving catalytic activity and electrochemical effective surface area.
Smart Images

Figure 0007647145000004 
Figure 0007647145000005 
Figure 0007647145000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a fuel cell catalyst and a manufacturing method thereof, and more particularly to a fuel cell catalyst in which Pt-containing nanowire particles are densely supported on the surface of a support, there is little aggregation of the nanowire particles on the support surface, and there is little decrease in activity due to catalyst poisoning, and a manufacturing method thereof. [Background technology]
[0002] A polymer electrolyte fuel cell comprises a membrane electrode assembly (MEA) in which electrodes (catalyst layers) containing a catalyst are bonded to both sides of an electrolyte membrane. A gas diffusion layer is usually disposed on the outside of the catalyst layer. A current collector (separator) having a gas flow path is also disposed on the outside of the gas diffusion layer. A polymer electrolyte fuel cell usually comprises a structure (fuel cell stack) in which a plurality of unit cells each consisting of such an MEA, gas diffusion layer, and current collector are stacked.
[0003] The electrode catalyst for a polymer electrolyte fuel cell is usually one in which catalyst particles are supported on the surface of a carrier. The catalyst particles are made of precious metals such as Pt, Pd, Ru, or alloys containing these metals. Since the electrode reaction occurs on the surface of the catalyst particles, if fine catalyst particles are supported on the surface of the carrier in a highly dispersed manner, the utilization rate of the precious metal is improved, and the amount of expensive precious metal used can be reduced. Therefore, various methods for producing and supporting fine catalyst particles have been proposed.
[0004] For example, Non-Patent Document 1 states: (a) Pt(acac)2, Ni(acac)2, cetyltrimethylammonium chloride (CTAC), and Mo(CO)6 were dissolved in oleylamine (OA); (b) Heat the resulting homogeneous solution in an oil bath at 160°C for 2 hours; (c) The colloidal product was collected by centrifugation and washed three times with a mixture of cyclohexane / ethanol (1:9, v / v). A method for producing Pt nanowires is disclosed.
[0005] Furthermore, Non-Patent Document 1 states: (a) supporting the thus obtained Pt nanowires on a carbon support surface; (b) Pt nanowires / C are washed three times with a cyclohexane / ethanol mixture. A catalyst obtained by the above process is disclosed.
[0006] The same document states: (A) such a method results in Pt nanowires with diameters of 0.8 nm and aspect ratios of about 22.5; and (B) The mass activity (MA), specific activity (SA), and electrochemically effective surface area (ECSA) of Pt nanowires / C are 1.06 A / mg and 1.39 mA / cm, respectively. 2 , and 76.4m 2 / g, is stated.
[0007] Pt nanowires can be synthesized by using the method described in Non-Patent Document 1. However, the method described in Non-Patent Document 1 does not allow Pt nanowires to be supported on the support surface at a high loading density without agglomerating the Pt nanowires. In addition, the Pt nanowire / C catalyst obtained by the method described in Non-Patent Document 1 has a relatively low catalytic activity. Furthermore, Ni compounds such as Ni(acac)2 are necessary components for the high activity of nanowire catalysts through alloying effect and surface control, but Ni or Ni compounds may remain in the catalyst depending on the manufacturing conditions. Ni alloyed with Pt has the effect of improving the catalytic activity of Pt, but Ni, Ni compounds, and Ni alloyed with Pt contained in the catalyst are easily eluted in the fuel cell environment and cause cationic contamination. [Prior art documents] [Non-patent literature]
[0008] [Non-Patent Document 1] Kezhu Jiang et al., Sci. Adv. 2017;3:e1601705 Summary of the Invention [Problem to be solved by the invention]
[0009] The problem that the present invention aims to solve is to provide a fuel cell catalyst and a method for producing the same, in which Pt-containing nanowire particles are densely supported on the surface of a support, there is little aggregation of the nanowire particles, and there is little decrease in activity due to catalyst poisoning. Another object of the present invention is to provide a fuel cell catalyst which causes less elution of metal ions, and a method for producing the same. [Means for solving the problem]
[0010] In order to solve the above problems, the fuel cell catalyst according to the present invention has the following configuration. (1) The fuel cell catalyst is A conductive carrier; nanowire particles containing Pt supported on the support surface; It is equipped with: (2) The nanowire particles are The short diameter is more than 0.8 nm and not more than 10 nm, The loading rate is 15 mass% or more and 50 mass% or less.
[0011] The method for producing a fuel cell catalyst according to the present invention has the following features. (1) The method for producing the fuel cell catalyst comprises the steps of: A first step of dispersing a Pt precursor, a Ni precursor, W(CO)6 and / or Mo(CO)6, and a nitrogen-containing surfactant in oleylamine to obtain a precursor solution; a second step of obtaining nanowire particle precursors, the surfaces of which are modified with the oleylamine, by holding the precursor solution at a temperature of 160° C. or higher and 190° C. or lower for 2 hours or longer; a third step of washing the nanowire particle precursor to obtain the nanowire particles from which a portion of the oleylamine modifying the surface has been removed; a fourth step of supporting the nanowire particles on a surface of a conductive support to obtain a catalyst precursor having the nanowire particles supported on the surface of the support; a fifth step of washing the catalyst precursor to further remove the oleylamine remaining on the surface of the nanowire particles, thereby obtaining a fuel cell catalyst according to the present invention; It is equipped with: (2) The third step comprises washing the nanowire particle precursor once with a cyclohexane / ethanol mixed solvent. (3) The fifth step comprises washing the catalyst precursor three or more times with a solvent consisting of at least one selected from the group consisting of aromatic hydrocarbons, cycloparaffins, and n-paraffins.
[0012] The method for producing the fuel cell catalyst includes: A sixth step of dissolving Ni contained in the fuel cell electrode catalyst by treating the fuel cell catalyst with an acid after the fifth step. It is preferable that the device further comprises: Effect of the Invention
[0013] If the nanowire particles are synthesized and then washed relatively weakly, the surface modifier oleylamine is not excessively removed, thereby suppressing the aggregation of the nanowire particles, and therefore the nanowire particles can be densely supported on the support surface without agglomeration. In addition, by performing relatively strong washing after supporting the nanowire particles on the support surface, the remaining surface modifier can be almost completely removed, thereby suppressing catalyst poisoning caused by the remaining surface modifier. Furthermore, by carrying out acid washing after supporting the nanowire particles on the support surface, the Ni remaining in the fuel cell catalyst can be almost completely removed, which makes it possible to suppress the dissolution of Ni from the catalyst in the fuel cell environment. [Brief description of the drawings]
[0014] [Figure 1] 1(A) is a STEM image of the catalyst obtained in Example 1. FIG. 1(B) is a STEM image of the catalyst obtained in Comparative Example 1. [Diagram 2] 1 is a TEM image of the catalyst obtained in Non-Patent Document 1 (cited from Non-Patent Document 1). [Diagram 3] 1 is a TEM image of the catalyst obtained in Example 1. [Figure 4] 1 is a STEM image of the nanowire particles (before support) obtained in Example 1.
[0015] [Diagram 5] Fig. 5(A) is a STEM image of the catalyst (before acid treatment) obtained in Example 1. Fig. 5(B) is a mapping image of Pt element of the same catalyst. Fig. 5(C) is an element mapping image of Ni of the same catalyst. [Figure 6] Fig. 6(A) is a STEM image of the catalyst (after acid treatment) obtained in Example 1. Fig. 6(B) is a mapping image of Pt element of the same catalyst. Fig. 6(C) is an element mapping image of Ni of the same catalyst. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] An embodiment of the present invention will be described in detail below. [1. Fuel cell catalyst] The fuel cell catalyst according to the present invention (hereinafter, simply referred to as "catalyst") is A conductive carrier; nanowire particles containing Pt supported on the support surface; It is equipped with:
[0017] [1.1. Carrier] The carrier is made of a conductive material. There is no particular limitation on the material of the carrier, so long as it is conductive and usable in the fuel cell operating environment. Examples of the material of the carrier include carbon black, carbon nanotubes, carbon nanohorns, activated carbon, natural graphite, mesocarbon microbeads, and glassy carbon powder.
[0018] [1.2. Nanowire particles] [1.2.1. Shape] In the present invention, the term "nanowire particles" refers to particles having a wire-like elongated shape and a diameter in the nanometer range. By using the method described below, nanowire particles having a short diameter of more than 0.8 nm and not more than 10 nm can be obtained. When the manufacturing conditions are optimized, the short diameter becomes greater than 0.8 nm and equal to or less than 3 nm. Similarly, when the manufacturing conditions are optimized, the length is 10 nm or more and 50 nm or less.
[0019] [1.2.2. Composition] In the present invention, the nanowire particles contain Pt. By using the method described below, nanowire particles having a Pt content of 90 mass% or more can be obtained. By optimizing the production conditions, the Pt content can be 95 mass% or more, or 98 mass% or more. Impurities that may be contained in nanowire particles include, for example, metal elements (eg, Ni, Mo, W, etc.) derived from the starting material.
[0020] [1.2.3. Loading rate] "Supporting ratio" refers to the ratio of the mass of nanowire particles to the total mass of the catalyst. In general, if the loading rate is too low, the amount of Pt per unit volume when a membrane electrode assembly (MEA) is produced will be small. Therefore, the thickness of the catalyst layer required to ensure a sufficient amount of Pt for power generation will be large. In general, the thicker the catalyst layer, the greater the resistance to mass transfer within the catalyst layer. Therefore, the loading rate must be 15 mass% or more. The loading rate is preferably 20 mass% or more, and more preferably 30 mass% or more. On the other hand, even if the loading rate is increased more than necessary, there is no difference in the effect and no practical benefit. Therefore, the loading rate must be 50 mass% or less.
[0021] [1.3. Characteristics] [1.3.1. ECSA (effective electrochemical surface area)] The fuel cell catalyst according to the present invention exhibits high ECSA because nanowire particles are densely supported on the support surface and the nanowire particles are less likely to aggregate. When the production conditions are optimized, the ECSA can reach 40m. 2 / g Pt More than 200m 2 / g Pt Further optimization of the production conditions results in a catalyst with an ECSA of 70m 2 / g Pt or more than 100m 2 / g Pt That's all.
[0022] [1.3.2. MA (activity per Pt mass)] The nanowire particles have a diameter of nanometer size, a large surface area per Pt mass, and a high density of highly active (111) faces, so they exhibit high MA. When the manufacturing conditions were optimized, the MA was increased to 500 A / g Pt More than 30000A / g Pt Further optimization of the preparation conditions results in a catalyst with a molecular weight of 875 A / g or less. Pt or more than 1250A / g Pt That's all.
[0023] [1.3.3. SA (specific activity)] The fuel cell catalyst according to the present invention exhibits high SA. When the production conditions are optimized, the SA can reach 1400 μA / cm 2 More than 15000μA / cm 2 Further optimization of the production conditions results in a catalyst with an SA of 1800 μA / cm 2 or more, or 2000μA / cm 2 That's all.
[0024] [1.3.4. Ni content] "Ni content" refers to the ratio of the mass of Ni to the total mass of the catalyst. In order to activate the nanowire catalyst by alloying effect and surface control, it is necessary to use Ni precursor such as Ni(acac)2. In this case, some of the Ni precursor used may remain in the catalyst as it is, or as Ni compounds or Ni generated by decomposition and reaction of the Ni precursor. Ni alloyed with Pt has the effect of improving the catalytic activity of Pt. However, Ni, Ni compounds, and Ni alloyed with Pt contained in the catalyst are easily dissolved in the fuel cell environment and may cause cationic contamination. In contrast, if the method described below is used, a catalyst with a Ni content of 1.5 mass% or less can be obtained. The lower the Ni content, the better. If the manufacturing conditions are optimized, the Ni content will be 0.01 mass% or less.
[0025] [2. Manufacturing method of fuel cell catalyst] The method for producing a fuel cell catalyst according to the present invention includes the steps of: A first step of dispersing a Pt precursor, a Ni precursor, W(CO)6 and / or Mo(CO)6, and a nitrogen-containing surfactant in oleylamine to obtain a precursor solution; a second step of obtaining nanowire particle precursors, the surfaces of which are modified with the oleylamine, by holding the precursor solution at a temperature of 160° C. or higher and 190° C. or lower for 2 hours or longer; a third step of washing the nanowire particle precursor to obtain the nanowire particles from which a portion of the oleylamine modifying the surface has been removed; a fourth step of supporting the nanowire particles on a surface of a conductive support to obtain a catalyst precursor having the nanowire particles supported on the surface of the support; a fifth step of washing the catalyst precursor to further remove the oleylamine remaining on the surface of the nanowire particles, thereby obtaining a fuel cell catalyst according to the present invention; It is equipped with:
[0026] The method for producing a fuel cell catalyst according to the present invention includes the steps of: A sixth step of dissolving Ni contained in the fuel cell electrode catalyst by treating the fuel cell catalyst with an acid after the fifth step. It may further comprise:
[0027] [2.1. 1st step] First, a Pt precursor, a Ni precursor, W(CO)6 and / or Mo(CO)6, and a nitrogen-containing surfactant are dispersed in oleylamine to obtain a precursor solution (first step).
[0028] 2.1.1. Ingredients The Pt precursor is the main raw material of nanowire particles. The type of Pt precursor is not particularly limited as long as it can synthesize nanowire particles. Examples of Pt precursors include platinum (II) acetylacetonate (Pt(acac)2), chloroplatinic acid (H2PtCl6), and tetraammineplatinum chloride (Pt(NH3)4Cl2).
[0029] The Ni precursor is a necessary component for high activation of nanowire catalysts due to alloying effect and surface control. If the precursor solution does not contain a strong reducing agent (e.g., glucose), the Ni precursor is usually not reduced, and nanowire particles consisting essentially of Pt alone are obtained. However, depending on the synthesis conditions, Ni or Ni compounds may be by-produced. The type of Ni precursor is not particularly limited as long as it can synthesize nanowire particles. Examples of Ni precursors include Ni(II) acetylacetonate (Ni(acac)2), nickel chloride (NiCl2), and nickel acetate (Ni(CH3COO)2).
[0030] W(CO)6 and Mo(CO)6 are components necessary for controlling the length and surface roughness of nanowire particles. The precursor solution may contain either W(CO)6 or Mo(CO)6, or may contain both. When W(CO)6 and / or Mo(CO)6 are added to the precursor solution, CO is released from W(CO)6 or Mo(CO)6. The released CO is repeatedly adsorbed and desorbed on the surface of the nanowire particle during growth. As a result, it is believed that the length of the nanowire particle and the surface roughness are controlled.
[0031] Nitrogen-containing surfactants are necessary components for growing Pt into wires. When nitrogen-containing surfactants are added to the precursor solution, rod-like micelles are generated, and it is believed that nanowire particles are generated by reducing the Pt precursor within the rod-like micelles. The type of nitrogen-containing surfactant is not particularly limited as long as it is capable of synthesizing nanowire particles. Examples of nitrogen-containing surfactants include cetyltrimethylammonium chloride (CTAC), cetyltrimethylammonium bromide (CTAB), and dodecyltrimethylammonium bromide (DDAB).
[0032] Oleylamine is (a) a solvent for dissolving the raw materials; (b) a reducing agent for reducing the Pt precursor, and (c) A surface modifier that adsorbs to the surface of nanowire particles and prevents the nanowire particles from agglomerating. It functions as: However, since the reducing power of oleylamine is relatively weak, the reduction of the Pt precursor proceeds but the reduction of the Ni precursor usually hardly proceeds.
[0033] [2.1.2. Concentration] The concentration of each component contained in the precursor solution is not particularly limited, and an optimal concentration can be selected depending on the purpose. Generally, if the concentration of the Pt precursor is too low, the yield of nanowire particles is low, so the concentration of the Pt precursor is preferably 0.24 mass% or more. On the other hand, even if the concentration of the Pt precursor is made higher than necessary, there is no difference in the effect and no practical benefit, so the concentration of the Pt precursor is preferably 0.48 mass% or less.
[0034] In general, if the concentration of the Ni precursor is too low, the high activity of the nanowire catalyst due to the alloying effect and surface control cannot be obtained, so the concentration of the Ni precursor is preferably 0.01 mass% or more. On the other hand, if the concentration of the Ni precursor is too high, the amount of Ni that is reduced increases, so the concentration of the Ni precursor is preferably 0.15 mass% or less.
[0035] Generally, if the total concentration of W(CO)6 and Mo(CO)6 is too low, nanowire particles cannot be collected. Therefore, the total concentration of W(CO)6 and Mo(CO)6 is preferably 0.07 mass% or more. On the other hand, even if the total concentration of W(CO)6 and Mo(CO)6 is increased more than necessary, there is no difference in the effect and no practical benefit. Therefore, the total concentration of W(CO)6 and Mo(CO)6 is preferably 0.7 mass% or less.
[0036] In general, if the concentration of the nitrogen-containing surfactant is too low, rod-like micelles cannot be formed and Pt does not grow into nanowires, so the concentration of the nitrogen-containing surfactant is preferably 0.39 mass% or more. On the other hand, if the concentration of the nitrogen-containing surfactant is made higher than necessary, there is no difference in the effect and no practical benefit, and therefore the concentration of the nitrogen-containing surfactant is preferably 3.0 mass% or less.
[0037] [2.2. 2nd process] Next, the precursor solution is held at a temperature of 160° C. to 190° C. for 2 hours or more (second step), thereby obtaining nanowire particle precursors in which the surfaces of the nanowire particles are modified with oleylamine.
[0038] If the treatment temperature is too low, the reduction reaction does not proceed, so the treatment temperature is preferably 160° C. or higher. On the other hand, if the treatment temperature is too high, the melting point of the surfactant may be reached and micelles may not be formed. Therefore, the treatment temperature is preferably 190° C. or lower.
[0039] If the treatment time is too short, the yield of nanowire particles decreases, so the treatment time is preferably 2 hours or more. On the other hand, if the treatment time is longer than necessary, there is no difference in the effect and no practical benefit, so it is preferable to select an optimal treatment time depending on the purpose.
[0040] [2.3. Third step] Next, the nanowire particle precursor is washed to obtain nanowire particles from which a portion of the oleylamine modifying the surface has been removed (third step).
[0041] Oleylamine is a necessary component for forming nanowire particles, but it is also a substance that poisons the active sites of the catalyst. In order to reduce catalyst poisoning, it is preferable to completely remove oleylamine from the surface of the nanowire particles. However, oleylamine also functions as a surface modifier that suppresses the aggregation of nanowire particles generated in the solution. Therefore, if the nanowire particles are washed under conditions that remove all of the oleylamine that modifies the surface of the nanowire particles before they are supported on the support surface after the reaction is completed, the nanowire particles are likely to aggregate.
[0042] Therefore, the washing before loading the nanowire particle precursor on the carrier surface must be performed under conditions that remove by-products and unreacted materials and also remove a portion of the oleylamine modifying the surface of the nanowire particle. In the present invention, the washing before loading is performed only once with a cyclohexane / ethanol mixed solvent. This is different from the conventional method. Cyclohexane / ethanol mixed solvent has a moderate cleaning power. Therefore, washing with cyclohexane / ethanol mixed solvent multiple times will remove too much oleylamine. Therefore, washing before loading is performed only once.
[0043] The content of cyclohexane in the mixed solvent is selected to be optimal depending on the purpose. In general, if the content of cyclohexane is too low, insufficient washing occurs. Therefore, the content of cyclohexane is preferably 10 vol% or more. On the other hand, even if the content of cyclohexane is increased more than necessary, there is no difference in the effect and no practical benefit, so the content of cyclohexane is preferably 50 vol% or less.
[0044] [2.4. 4th step] Next, the nanowire particles are supported on the surface of a conductive support (fourth step), thereby obtaining a catalyst precursor having the nanowire particles supported on the surface of the support. The method of supporting nanowire particles on the carrier surface is not particularly limited. For example, when the nanowire particle precursor and the carrier are dispersed in a solvent and ultrasonic waves are applied, the nanowire particle precursor and the carrier are uniformly dispersed, and at the same time, the oleylamine on the nanowire particle surface is gradually removed by the solvent. Furthermore, when most of the oleylamine on the nanowire particle surface is removed, the nanowire particles are attached onto the carrier. As a result, the nanowire particles can be supported on the carrier surface.
[0045] [2.5. 5th step] Next, the catalyst precursor is washed to further remove any oleylamine remaining on the surfaces of the nanowire particles (step 5), thereby obtaining the fuel cell catalyst according to the present invention.
[0046] As mentioned above, oleylamine is a surface modifier for suppressing aggregation, and at the same time, it is also a substance that causes catalyst poisoning. In order to reduce catalyst poisoning, it is preferable to wash the nanowire particles after they are supported on the support surface under conditions that allow the oleylamine remaining on the surface of the nanowire particles to be almost completely removed. "Almost completely removed" means that the SA of the catalyst after washing is 1400 μA / cm 2 This means that the above is the case. In the present invention, the catalyst precursor is washed three or more times after the loading with a solvent consisting of at least one selected from the group consisting of aromatic hydrocarbons, cycloparaffins, and n-paraffins, which is different from the conventional method.
[0047] Aromatic hydrocarbons, cycloparaffins, and n-paraffins all have stronger cleaning power than the cyclohexane / ethanol mixed solvent, so washing the catalyst precursor with these solvents can remove most of the remaining oleylamine. The above solvents have strong cleaning power, so that a sufficient effect can be obtained even with one cleaning. However, generally, the more the number of cleanings, the less the amount of oleylamine remaining. In order to reduce catalyst poisoning, the number of cleanings must be three or more. The number of cleanings is preferably five or more.
[0048] [2.6. 6th step] Next, if necessary, the fuel cell catalyst is treated with an acid (sixth step), which allows Ni contained in the fuel cell catalyst to be eluted.
[0049] Oleylamine also functions as a reducing agent, but its reducing power is relatively weak. Therefore, the Ni precursor in the precursor solution is usually hardly reduced. However, depending on the manufacturing conditions, Ni or Ni compounds may be mixed into the catalyst. Ni alloyed with Pt has the effect of improving the catalytic activity of Pt, but Ni, Ni compounds, and Ni alloyed with Pt contained in the catalyst are easily eluted in the fuel cell environment and may cause cationic contamination. In order to suppress the elution of Ni, it is preferable to previously wash the catalyst with an acid to remove the remaining Ni.
[0050] The conditions of the acid treatment are not particularly limited as long as the remaining Ni can be removed. For example, most of the remaining Ni can be removed by adding the fuel cell catalyst to a 1M aqueous sulfuric acid solution and stirring for 12 hours. After the acid treatment, the fuel cell catalyst is recovered, washed and dried.
[0051] [3. Effect] Oleylamine functions as a surface modifier that prevents the aggregation of nanowire particles. After synthesizing nanowire particles in the presence of oleylamine, washing the nanowire particles three times with a cyclohexane / ethanol mixed solvent results in excessive removal of oleylamine from the nanowire particle surface. This makes it difficult to suppress the aggregation of nanowire particles, and makes it difficult to support nanowire particles on the support surface at high density and high dispersion.
[0052] Next, even if the nanowire particles are supported on the support surface and washed three times with a cyclohexane / ethanol mixed solvent, the oleylamine remaining on the surface of the nanowire particles cannot be completely removed. The remaining oleylamine blocks (poisons) the active sites of the catalyst, causing a decrease in catalytic activity. Furthermore, when a Ni precursor is used to activate the nanowire catalyst by alloying effect and surface control, Ni or Ni compounds may be included in the catalyst depending on the manufacturing conditions. Ni, Ni compounds, and Ni alloyed with Pt are easily dissolved in the fuel cell environment and cause cationic contamination.
[0053] In contrast, if the nanowire particles are synthesized and then washed relatively weakly, the surface modifier oleylamine is not removed excessively, thereby suppressing the aggregation of the nanowire particles, and the nanowire particles can be densely supported on the support surface without agglomeration. In addition, by performing relatively strong washing after supporting the nanowire particles on the support surface, the remaining surface modifier can be almost completely removed, thereby suppressing catalyst poisoning caused by the remaining surface modifier. Furthermore, by carrying out acid washing after supporting the nanowire particles on the support surface, the Ni remaining in the fuel cell catalyst can be almost completely removed, which makes it possible to suppress the dissolution of Ni from the catalyst in the fuel cell environment. EXAMPLES
[0054] (Example 1, Comparative Example 1) [1. Sample preparation] 1.1. Example 1 Pt(acac)2, Ni(acac)2, Mo(CO)6, and cetyltrimethylammonium chloride (CTAC) were ultrasonically dispersed in oleylamine to obtain a precursor solution. The precursor solution was heated to 160°C and held for 2 hours. It was then gradually cooled to room temperature to obtain a colloidal solution in which nanowire particles containing Pt were dispersed. The nanowire particles were recovered from the colloidal solution and washed once with a cyclohexane / ethanol mixed solvent (volume ratio=1:9) to remove unreacted materials and a portion of the surface modifier.
[0055] Next, the washed nanowire particles and the carbon support were dispersed in a cyclohexane / ethanol mixed solvent (volume ratio = 1:1) and ultrasonically irradiated for 1 hour to support the nanowire particles on the surface of the carbon support. The nanowire particle-supported carbon (hereinafter also referred to as "nanowire particles / C") was recovered from the dispersion and the nanowire particles / C was washed five times with toluene. After washing, the solvent was replaced with ethanol, and the nanowire particles / C were suction filtered and dried at 80° C. Furthermore, the dried catalyst was stirred in 1M sulfuric acid at room temperature for 12 hours to remove Ni from the catalyst.
[0056] [1.1. Comparative Example 1] A catalyst was synthesized by simulating Non-Patent Document 1. Pt(acac)2, Ni(acac)2, Mo(CO)6, and CTAC were ultrasonically dispersed in oleylamine to obtain a precursor solution. The precursor solution was heated to 160°C and held for 2 hours. It was then gradually cooled to room temperature to obtain a colloidal solution in which nanowire particles containing Pt were dispersed. The nanowire particles were recovered from the colloidal solution and washed three times with a cyclohexane / ethanol mixed solvent (volume ratio=1:9) to remove unreacted materials and the surface modifier.
[0057] Next, the washed nanowire particles and the carbon support were dispersed in a cyclohexane / ethanol mixed solvent (volume ratio = 1:1) and ultrasonically irradiated for 1 hour to support the nanowire particles on the carbon support surface. The nanowire particles / C were recovered from the dispersion and washed three times with a cyclohexane / ethanol mixed solvent (volume ratio = 1:9). After washing, the solvent was replaced with ethanol, and the nanowire particles / C were filtered by suction and dried at 80°C.
[0058] 2. Test Method [2.1. TEM and STEM observations, and composition analysis] The catalysts were observed using a transmission electron microscope (TEM) and a scanning transmission electron microscope (STEM). In addition, the composition of the obtained catalyst was analyzed using an inductively coupled plasma mass spectrometer (ICP-MS).
[0059] [2.2. Electrochemical evaluation] The catalyst was electrochemically evaluated using a rotating disk electrode (RDE). The cell was a three-electrode type, and 0.1M HClO4 was used as the electrolyte. A reversible hydrogen electrode (RHE) and a black Pt mesh were used as the reference and counter electrodes, respectively. The working electrode was immersed in an electrolyte saturated with Ar, and potential cycling was performed between 0.05 V and 1.2 V (RHE) until the cyclic voltammogram (CV) stabilized. Then, the electrolyte was saturated with O2, and a linear sweep voltammogram (LSV, positive potential sweep, sweep rate: 10 mV / s) was performed while rotating the electrode at 1600 rpm.
[0060] [3. Results] [3.1. TEM and STEM observations, and composition analysis] [3.1.1. Support state of nanowire particles] Fig. 1(A) shows a STEM image of the catalyst obtained in Example 1. Fig. 1(B) shows a STEM image of the catalyst obtained in Comparative Example 1. In Example 1, the nanowire particles were uniformly supported on the surface of the carbon support. On the other hand, in Comparative Example 1, there were areas where the nanowire particles were aggregated and areas where the nanowire particles were not supported.
[0061] In Comparative Example 1, the nanowire particles were washed three times with a cyclohexane / ethanol mixed solvent (volume ratio = 1:9) before loading. This method removes too much of the surface modifier from the nanowire particles before loading, which is thought to cause aggregation of the nanowire particles before loading, resulting in the nanowire particles being loaded on the carbon support surface in an aggregated state. In contrast, in Example 1, washing before loading was performed only once, and therefore the surface modifier was not removed excessively, which is believed to have suppressed aggregation of the nanowire particles.
[0062] [3.1.2. Nanowire particle loading rate] Figure 2 shows a TEM image (cited from Non-Patent Document 1) of the catalyst obtained in Non-Patent Document 1. Figure 3 shows a TEM image of the catalyst obtained in Example 1. In Figures 2 and 3, the carbon particles surrounded by white circles each represent particles that are not overlapped with other carbon particles. In the case of FIG. 2, the number of nanowire particles on the surfaces of the five carbon particles surrounded by white circles was 17. On the other hand, in the case of FIG. 3, the number of nanowire particles on the surfaces of the five carbon particles surrounded by white circles was 24. Therefore, the number of nanowire particles per support in Example 1 is considered to be greater than that in Non-Patent Document 1. In other words, the loading rate of nanowire particles in Example 1 is considered to be higher than that in Non-Patent Document 1.
[0063] The loading rate of Example 1 was analyzed by ICP. As a result, the loading rate was 19.7 mass%. Non-Patent Document 1 does not disclose the loading rate, but it is believed to have been lower than this. Also, in Non-Patent Document 1, it is believed that the amount of nanowire particles charged relative to the carbon particles during loading was small.
[0064] [3.1.3. Shape of nanowire particles] Figure 4 shows a STEM image of the nanowire particles (before support) obtained in Example 1. In Figure 4, the short diameter of 30 randomly selected nanowire particles was examined. As a result, the average short diameter was 1.2 nm, which was larger than that (0.8 nm) in Non-Patent Document 1.
[0065] [3.1.4. Acid treatment] Fig. 5(A) shows a STEM image of the catalyst obtained in Example 1 (before acid treatment). Fig. 5(B) shows a mapping image of Pt element of the same catalyst. Fig. 5(C) shows an element mapping image of Ni of the same catalyst. Furthermore, Table 1 shows the results of quantitative analysis performed on the catalyst obtained in Example 1 (before acid treatment) within the area enclosed by the square in Fig. 5(A). It can be seen from Figure 5 that not only nanowire particles but also several spherical particles of different diameters are supported on the carbon surface. Also, from Figures 5(B), 5(C) and Table 1, it can be seen that the spherical particles with a diameter of about 30 nm are Ni.
[0066] [Table 1]
[0067] Fig. 6(A) shows a STEM image of the catalyst (after acid treatment) obtained in Example 1. Fig. 6(B) shows a mapping image of Pt element of the same catalyst. Fig. 6(C) shows an element mapping image of Ni of the same catalyst. As shown in FIG. 6, no large particles with a particle size of about 30 nm were observed in the catalyst after the acid treatment, and it is believed that Ni was dissolved by the acid treatment. Table 2 shows the results of ICP-MS analysis of the catalyst obtained in Example 1 (after acid treatment).
[0068] [Table 2]
[0069] Ni was found in the catalyst before acid treatment, and it is thought that if the catalyst before acid treatment is used in a fuel cell environment as is, this Ni will dissolve and act as cationic contamination, causing a decrease in fuel cell performance. In contrast, if a final acid treatment is performed, Ni can be eluted, which is thought to suppress the performance degradation caused by cationic contamination.
[0070] [3.2. Electrochemical evaluation] Table 3 shows the electrochemical surface area (ECSA), Pt gravimetric activity (MA), and specific activity (SA) of the catalysts obtained in Example 1 and Comparative Example 1. Table 3 also shows the values disclosed in Non-Patent Document 1. The following can be seen from Table 3.
[0071] (1) The MA and SA of Comparative Example 1 are lower than those of Example 1. One of the reasons for this is thought to be catalyst poisoning due to insufficient washing after loading. In Comparative Example 1, washing is performed with a cyclohexane / ethanol mixed solvent after loading. However, the cleaning power of the solvent is weak and the number of washings is small, so it is thought that the surface modifier remains and blocks the active sites on the catalyst surface. (2) In Example 1, the catalyst after support was washed five times with toluene, an organic solvent with stronger cleaning power, which is believed to have sufficiently removed the surface modifier, resulting in high activity.
[0072] (3) Comparative Example 1 has a smaller ECSA than Example 1. This is believed to be due to the fact that the nanowire particles aggregated as described above, which reduced the catalyst utilization rate. As a result, the MA (= the product of ECSA and SA) of Comparative Example 1 was smaller than that of Example 1. (4) The ECSA of Example 1 is smaller than that of Non-Patent Document 1. This is believed to be because the short diameter of the nanowire particles obtained in Example 1 is larger than that of Non-Patent Document 1.
[0073] (5) The MA of Example 1 was comparable to that of Non-Patent Document 1. On the other hand, the SA of Example 1 was greater than that of Non-Patent Document 1. This result suggests that in Non-Patent Document 1, cleaning after loading was insufficient, and the surface modifier remained on the catalyst surface and around it. (6) Although the loading rate is not described in Non-Patent Document 1, the STEM image as described above suggests that the loading rate in Non-Patent Document 1 is lower than that in Example 1. If the loading rate in Non-Patent Document 1 were to be the same as that in Example 1, it is believed that the particles would aggregate due to the large number of washings before loading, resulting in a decrease in activity. In addition, when an MEA is produced using a catalyst with a low loading rate, if the platinum weight is the same, the catalyst layer will be thicker than when a catalyst with a high loading rate is used, and the high current range performance will be lower.
[0074] [Table 3]
[0075] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]
[0076] The fuel cell catalyst according to the present invention can be used as an electrode catalyst for the air electrode and / or fuel electrode of a polymer electrolyte fuel cell used in, for example, a power source for an automobile or a small stationary generator.
Claims
1. A fuel cell catalyst comprising: (1) The fuel cell catalyst is A conductive carrier; nanowire particles including Pt supported on the support surface; It is equipped with: (2) The nanowire particles are The short diameter is more than 0.8 nm and not more than 10 nm, The length is 10 nm or more and 50 nm or less, The loading rate is 15 mass % or more and 50 mass % or less. (3) The fuel cell catalyst has an MA (activity per Pt mass) of 500 A / g Pt More than 30000A / g Pt The following is the result.
2. ECSA (effective electrochemical surface area) is 40m 2 / g Pt More than 200m 2 / g Pt 2. The fuel cell catalyst of claim 1, wherein:
3. SA (specific activity) is 1400 μA / cm 2 More than 15000μA / cm 2 3. The fuel cell catalyst according to claim 1, wherein:
4. 4. The fuel cell catalyst according to claim 1, wherein the Ni content is 1.5 mass % or less.
5. A method for producing a fuel cell catalyst comprising the following steps: (1) The method for producing the fuel cell catalyst includes the steps of: Pt precursor, Ni precursor, W(CO) 6 and / or Mo(CO) 6 and a first step of dispersing a nitrogen-containing surfactant in oleylamine to obtain a precursor solution; a second step of obtaining nanowire particle precursors in which the surfaces of nanowire particles are modified with the oleylamine by holding the precursor solution at a temperature of 160° C. or higher and 190° C. or lower for 2 hours or more; a third step of washing the nanowire particle precursor to obtain the nanowire particles from which a portion of the oleylamine modifying the surface has been removed; a fourth step of supporting the nanowire particles on a surface of a conductive support to obtain a catalyst precursor having the nanowire particles supported on the surface of the support; a fifth step of washing the catalyst precursor to further remove the oleylamine remaining on the surface of the nanowire particles, thereby obtaining the fuel cell catalyst according to any one of claims 1 to 3; It is equipped with: (2) The third step comprises washing the nanowire particle precursor once with a cyclohexane / ethanol mixed solvent. (3) The fifth step comprises washing the catalyst precursor three or more times with a solvent consisting of at least one selected from the group consisting of aromatic hydrocarbons, cycloparaffins, and n-paraffins.
6. 6. The method for producing a fuel cell catalyst according to claim 5, further comprising a sixth step of, after the fifth step, subjecting the fuel cell catalyst to an acid treatment to dissolve Ni contained in the fuel cell catalyst, thereby obtaining the fuel cell catalyst according to claim 4.
Citation Information
Patent Citations
Catalyst for a fuel cell, a method for preparing the same, and a membrane-electrode assembly for a fuel cell including the same
US20070099069A1
Method for Removing Strongly Adsorbed Surfactants and Capping Agents from Metal to Facilitate their Catalytic Applications
US20130178357A1
Ultrafine nanowires as highly efficient electrocatalysts
US20190226120A1